Ekonomi - Mohamed Nasser Katib; Lim, Hock Eam; Noor Sa'adah Sabudin; Selamah Maamor; Siti Hadijah Che Mat; Nur Annizah Ishak; Emilda Hashim; Arnold, Roger A. (Cencage Learning Asia, 2012)
Buku ini meliputi hampir semua topik ekonomi asas yang merangkumi mikroekonomi dan makroekonomi.